2012
DOI: 10.1007/s00467-012-2113-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural history of bilateral mild isolated antenatal hydronephrosis conservatively managed

Abstract: Antibiotic prophylaxis and VCUG are not mandatory in newborns with bilateral mild isolated antenatal hydronephrosis, but clinical and ultrasound follow-up are recommended during the first year of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 35 publications
1
41
1
1
Order By: Relevance
“…Alconcher et al [12] reported that 80% of units resolved within the first 12 months of life. Others have reported intervals to resolution of 13.4 months–17 months [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Alconcher et al [12] reported that 80% of units resolved within the first 12 months of life. Others have reported intervals to resolution of 13.4 months–17 months [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors support initial conservative treatment of bilateral UPJO when it is diagnosed prenatally [8, 9]. A previous study showed that spontaneous improvement can be expected in most bilateral cases [9]. However, no clear protocol was established in that study.…”
Section: Introductionmentioning
confidence: 77%
“…Therefore, the natural history and appropriate management of contralateral hydronephrosis has received little attention. Several authors support initial conservative treatment of bilateral UPJO when it is diagnosed prenatally [8, 9]. A previous study showed that spontaneous improvement can be expected in most bilateral cases [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Se ha identificado que el riesgo de infección urinaria está presente aún hasta en el 9% de casos con hidronefrosis bilateral leve, además de no variar la presencia de reflujo vesicoureteral cuando la hidronefrosis es leve bilateral o unilateral 32 . Son diversos los resultados según el grupo estudiado, ya que mientras en algunos grupos hasta el 80% de los casos de hidronefrosis resuelven de forma espontánea, en otros se encuentran frecuentes complicaciones asociadas.…”
unclassified